Government Policy Strategies for Coastal Abrasion Management: A Case Study of Meranti Islands Regency, Riau Province - Wardana, Data; Sasmi, Dini Tiara (Kemudi, 2025)
This research aims to find out the government's strategy in overcoming abrasion in the Meranti Islands Regency, Riau Province. Abrasion is a serious problem faced by areas located in coastal areas. the problem of abrasion is a natural process in which the coastline is gradually eroded and eroded by the forces of waves, currents and tides. Other problems are also caused by human activity factors, such as over-exploitation of marine ecosystems that are usually the first line of defense against abrasion. This research uses qualitative methods to understand the various concepts found in the research process in the form of written words and the results of interviews with informants and behavior observed by observation, interviews and documentation of research results. The policy strategy is carried out by setting program objectives in the long term such as maintaining mangrove forests and community empowerment. then maintain the environment by issuing policies. In addition, persuasive strategies are needed in the form of guidance to the community. local governments also become facilitators in disaster management and environmental maintenance by collaborating with all parties.